Modernisation of Chinese Culture : Continuity and Change. - Rosker, Jana S. (Cambridge Scholars Publishing, 2013)
The editors are grateful to the Chiang Ching-kuo Foundation for its generous support of their research work which enabled them to publish the present book. The present book carefully maps the Chinese modernisation discourse, highlighting its relationship to other, similar discourses, and situating it within historical and theoretical contexts. In contrast to the majority of recent discussions of a ""Chinese development model"" that tend to focus more on institutional then cultural factors, and ...